ANALISIS PENGARUH KUALITAS LAYANAN, HARAPAN KINERJA DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (STUDI PADA RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG) - Nafisa, Jihan; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2018)
The study aims to examine and explain the effect of the variable company’s service quality, company’s performance perceived by customer, company’s image to the customer’s satisfaction and loyalty. The research was conducted in Islamic Hospital of Sultan Agung Semarang Central Jav. The objects chosen for the research were 155 patients of the hospital. The analysis tools are multiple regression and path analysis to determine the pattern and effect relationships between variables in sequence, i.e. independents, dependents and intervening variables. The results of the study explained that all 7 hypothesis are accepted. However the customer satisfaction finally is detected as not as intervening variable as it doesn’t increase the effect of independent variable (company’s service quality, company’s performance perceived by customer, company’s image) to customer’s loyalty. The direct effect of independent variables (company’s service quality, company’s performance perceived by customer, company’s image) to customer’s loyalty is bigger than their indirect effect through customer satisfaction.